2023
DOI: 10.1021/acscentsci.3c00040
|View full text |Cite
|
Sign up to set email alerts
|

PGL-III, a Rare Intermediate of Mycobacterium leprae Phenolic Glycolipid Biosynthesis, Is a Potent Mincle Ligand

Abstract: Although leprosy (Hansen's disease) is one of the oldest known diseases, the pathogenicity of Mycobacterium leprae (M. leprae) remains enigmatic. Indeed, the cell wall components responsible for the immune response against M. leprae are as yet largely unidentified. We reveal here phenolic glycolipid-III (PGL-III) as an M. leprae-specific ligand for the immune receptor Mincle. PGL-III is a scarcely present trisaccharide intermediate in the biosynthetic pathway to PGL-I, an abundant and characteristic M. leprae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While a core monosaccharide anchors the ligand at Ca 2+ site II, proximal amino acids establish contacts with additional carbohydrate residues, as well as conjugated peptides and lipids, increasing affinity of the interaction [58] . This is particularly well illustrated by the dependency of mincle‐induced signaling on oligosaccharides di‐esterized with branched fatty acids, such as trehalose dimycolate (TDM) and phenolic glycolipid‐III (PGL‐III) [57,59,60] . Several X‐ray crystallographic and NMR studies of human and bovine mincle indicated that the interaction with these glycolipids involves Ca 2+ ‐dependent binding of the first glucose, an additional proximal binding site for the second glucose, as well as a hydrophobic grove for lipid binding [54–57,61,62] (Figure 2c).…”
Section: Canonical Glycan Bindingmentioning
confidence: 93%
See 1 more Smart Citation
“…While a core monosaccharide anchors the ligand at Ca 2+ site II, proximal amino acids establish contacts with additional carbohydrate residues, as well as conjugated peptides and lipids, increasing affinity of the interaction [58] . This is particularly well illustrated by the dependency of mincle‐induced signaling on oligosaccharides di‐esterized with branched fatty acids, such as trehalose dimycolate (TDM) and phenolic glycolipid‐III (PGL‐III) [57,59,60] . Several X‐ray crystallographic and NMR studies of human and bovine mincle indicated that the interaction with these glycolipids involves Ca 2+ ‐dependent binding of the first glucose, an additional proximal binding site for the second glucose, as well as a hydrophobic grove for lipid binding [54–57,61,62] (Figure 2c).…”
Section: Canonical Glycan Bindingmentioning
confidence: 93%
“…[58] This is particularly well illustrated by the dependency of mincle-induced signaling on oligosaccharides diesterized with branched fatty acids, such as trehalose dimycolate (TDM) and phenolic glycolipid-III (PGL-III). [57,59,60] Several Xray crystallographic and NMR studies of human and bovine mincle indicated that the interaction with these glycolipids involves Ca 2 + -dependent binding of the first glucose, an additional proximal binding site for the second glucose, as well as a hydrophobic grove for lipid binding [54][55][56][57]61,62] (Figure 2c). Since these extended recognition interfaces are less conserved, they also provide selectivity, even between closely related CLRs, such as DC-SIGN and its mouse homologs SIGN-R1, 2, 3, 4, 5, 7, and 8.…”
Section: Canonical Glycan Bindingmentioning
confidence: 99%
“…Three major classes of MA are alpha (α-) MA, keto-MA, and methoxy (MeO-) MA (Figure A) , and play an important role both as a physical barrier and in infection biology . Another recent addition is the phenolic glycolipid (PGL), shown to boost acquired immune responses as an adjuvant in vivo . PGL is a surface lipid and glycosylated version of phthiocerol dimycocerosate (PDIM)the most extensively studied mycobacterial virulent lipid. , Its structure is composed of saccharide units (1–3 units) bound to a phenyl group, a mycocerosic acid and a phthiocerol region, Figure B.…”
Section: Introductionmentioning
confidence: 99%